2009
DOI: 10.1111/j.1502-3885.2008.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate and human induced hydrological change since AD 800 in an ombrotrophic mire in Pomerania (N Poland) tracked by testate amoebae, macro‐fossils, pollen and tree rings of pine

Abstract: This high‐resolution, multiproxy, palaeoenvironmental study of the Słowińskie Błota raised bog in N Poland, 10 km from the Baltic Sea, covering the last 1200 years reveals different aspects of environmental change in a range of spatial scales from local to regional. Testate amoebae allowed quantitative reconstruction of the local water table using a transfer function based on a training set from N and W Poland. Special attention is paid to the testate amoeba Arcella discoides, which responds to rapid water‐tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 53 publications
3
63
2
1
Order By: Relevance
“…Nevertheless, it is possible that in this part of Europe, the situation was different, and the Medieval Warm Period started earlier. Having no data from this part of Poland, we can compare our results with those obtained from northern Poland, from a Baltic bog in Stą _ zki (Lamentowicz et al, 2009). At this site, the water table remained high until AD 1000-1100, and later, it decreased and became very unstable.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, it is possible that in this part of Europe, the situation was different, and the Medieval Warm Period started earlier. Having no data from this part of Poland, we can compare our results with those obtained from northern Poland, from a Baltic bog in Stą _ zki (Lamentowicz et al, 2009). At this site, the water table remained high until AD 1000-1100, and later, it decreased and became very unstable.…”
Section: Discussionmentioning
confidence: 89%
“…Wilmshurst et al (2002) showed that peatlands in New Zealand were affected by change in forest composition, resulting in strong relationships between water table changes and pollen data. Studies in Poland revealed that moisture changes in raised bogs and kettle-hole bogs were correlated with deforestation phases (Lamentowicz et al, 2007a(Lamentowicz et al, , 2007b(Lamentowicz et al, , 2008b(Lamentowicz et al, , 2008c. There are, however, no indications for deforestation around Mauntschas mire, so wetness and vegetation changes in the mire should rather be interpreted in terms of climate change, although we cannot exclude the influence of minor changes in the surrounding forest on the hydrology.…”
Section: Surface Wetness and Vegetation Changesmentioning
confidence: 99%
“…The vegetation characteristics (i.e., Sphagnum dominance, see Section 2) described in Herbichowa (1998), and more recently in Lamentowicz et al (2008) and De Vleeschouwer et al (2009) indicate the presence of acidic, nutrient-poor conditions and strongly support the ombrotrophic character of the bog. Moreover, Herbichowa (1998) reported that the dome of the bog is elevated at ca.…”
Section: Ombrotrophymentioning
confidence: 99%